2020
DOI: 10.1126/sciadv.abb6546
|View full text |Cite
|
Sign up to set email alerts
|

Remobilization of dormant carbon from Siberian-Arctic permafrost during three past warming events

Abstract: Carbon cycle models suggest that past warming events in the Arctic may have caused large-scale permafrost thaw and carbon remobilization, thus affecting atmospheric CO2 levels. However, observational records are sparse, preventing spatially extensive and time-continuous reconstructions of permafrost carbon release during the late Pleistocene and early Holocene. Using carbon isotopes and biomarkers, we demonstrate that the three most recent warming events recorded in Greenland ice cores—(i) Dansgaard-Oeschger e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 43 publications
3
44
1
Order By: Relevance
“…Soil microbes could use these inventories to release greenhouse gases (GHG), which will accelerate climate warming and is known as the permafrost-carbon feedback (Schuur et al, 2015). It was shown that extensive remobilization of organic matter (OM) stored in permafrost occurred during the last major warming period at the Pleistocene-Holocene transition (Martens et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbes could use these inventories to release greenhouse gases (GHG), which will accelerate climate warming and is known as the permafrost-carbon feedback (Schuur et al, 2015). It was shown that extensive remobilization of organic matter (OM) stored in permafrost occurred during the last major warming period at the Pleistocene-Holocene transition (Martens et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Permafrost degradation has been reshaping or modifying northern and highland ecosystems, and the soil-vegetation systems in particular. More interests are focused on the topic not only due to the direct ecosystematic responses to permafrost degradation, but also to indirect scopes to understand carbon cycles and fluxes upon permafrost thaw, particularly abrupt permafrost thaw (e.g., [16,29,35,[196][197][198][199]). Permafrost degradation results in a loss of some boreal forests, shifts in plant composition and productivity, plant diversity, and changes in vegetation communities from terrestrial to wetlands, or from alpine meadows to alpine steppes or further to alpine deserts, through the changing dynamics of permafrost ecohydrology, soil nutrients, and soil biogeochemistry in a deepening active layer [16,29].…”
Section: Ecological Impacts and Adaptionmentioning
confidence: 99%
“…Permafrost thaw over the last few decades and its impacts may have modified the thermal regimes in the otherwise heat-conduction-dominated system (e.g., [25][26][27]), facilitating permafrost degradation and climate warming. Thus, a better understanding of the hydrogeological changes induced by climate warming and permafrost thaw is key to predicting and evaluating the changing ecosystem structures, dynamics, and serviceability at varied scales [28,29], especially for improving our ability to quantify and predict carbon (C) and nitrogen (N) fluxes [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In the Arctic, the East Siberian and Laptev Sea harbor methane deposits. Arctic warming by a few degrees Celsius may lead to permafrost thawing, coastal erosion, and the release of methane and CO 2 into the atmosphere, likely further worsening global warming 50 .…”
Section: Climate Changementioning
confidence: 99%